Desenvolvimento da ferramenta MS2PSOC: Tradução de modelos descritos no matlab/simulink para o ambiente psoc creator - Almeida, Alexandre Araujo Amaral de [UNESP] (2015)
Usually, a system is modeled in Simulink and later in PSoC Creator to deploy it in hardware PSoC. We present in this work a computational tool called MS 2 PSoC which analyses a model developed at a high level of abstraction in Matlab/Simulink and translates it to the PSoC Creator software. The goal of this translation is to implement the model in embedded system with PSoC technology. In the translation process, the MS 2 PSoC tool also generates the file structure needed for the translated model to be open in PSoC Creator. The innovation of this work is to allow the model to be simulated before it is implemented in hardware, given that the PSoC Creator software has no simulator. As a case study was used a MLT-3 line code, a D/A converter Ladder R-2R and a temperature control system for vehicles. The systems were implemented in PSoC hardware and evaluated by comparing them with the results obtained in the Simulink simulations. With the results it was concluded that the tool MS 2 PSoC correctly translates the models described in Matlab/Simulink environment for PSoC Creator, automating the deployment models in embedded system PSoC